Improved Training Sequence Channel Estimation Scheme in 16QAM MB-OFDM UWBoF System - Changqing Xiang; Xi Yang; Xuan Zhou; Xiaojun Zhu; Jincan Xu; Qiong He (Advances in Condensed Matter Physics)
In this paper, an improved channel estimation scheme based on time-domain orthogonal gray complementary training sequence (Golay TS) is proposed to resist subcarrier mutual beat interference in 16-quadrature amplitude modulation multiband orthogonal-frequency-division-multiplexing ultrawide band over fiber (16QAM MB-OFDM UWBoF) systems. The simulation results showed that the performance of system with the improved Golay TS channel estimation scheme was improved by about 1 dB compared with the traditional Golay TS channel estimation scheme, at a bit error rate (BER) of 3.8 × 10−3 after 70 km standard single mode fiber (SSMF) transmission. At the same time, the synchronization and channel estimation performance of Golay TS and the selected frequency-domain orthogonal training sequences (TSs) were compared. The simulation results showed that the performance of system with the TSs channel estimation was improved by about 2.7 dB compared with the improved Golay TS channel estimation.